PRODUCTIVITY MEASUREMENT ANALYSIS USING OMAX AND AHP METHODS ON BATIK SME - Chauliah Fatma Putri; Muhammad Agus Sahbana (Center for Study and Journal Management FTI UMI, 2022)
Batik is a cultural heritage originating from Indonesia which has been designated by UNESCO. Since then, the business of making batik has grown rapidly in Indonesia, with each region having its characteristics. In making batik, there are two kinds of manufacturing processes, namely the manufacturing production process and the traditional manufacturing process. Batik production is a unique process because it contains works of art with a traditional manufacturing process and contains elements of local policies. The difference in the manufacturing production process using modern technology, the resulting batik products also have the same results and can produce a lot of batik cloth in a short processing time. As for the process of making traditional batik, it must be produced one by one using traditional equipment, the batik pattern of each cloth is different, for the results cannot be identified this makes it special, and each stage of the process takes quite a long time. Productivity is important for batik production. Especially done by craftsmen in areas that are relatively new to developing traditional batik since the era of world cultural heritage has only been accepted by Indonesia. This study measures the productivity of BM batik SME in Malang. Based on the calculation and analysis of productivity using the Objective Matrix (OMAX) method for BM Batik SME, it can be concluded that the productivity of SME is low, with the lowest being the productivity of batik working time (value 1), the productivity of batik products having (value 1). 3) and labor productivity (score 5). With fishbone diagram analysis, it can be found the cause of the low productivity of these traditional batik SME. From here, several alternative solutions can be obtained, as recommendations for efforts to increase the productivity of SME based on traditional production without eliminating the heritage standards of batik works.